Informality and minimum wages by cohort in colombia. (2014)
This article aims to analyze the effect of minimum wage levels on the decision tojoin the informal job sector. We estimated a pseudo panel model of engagementin the informal sector using an IV-probit. Our results show that an increased wagegap—the relative difference between observed and minimum wage—has not onlya disincentive effect on the probability of joining informality, but also leads to asubstitution effect between younger and older cohorts.